2020
DOI: 10.5994/jei.17.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Pollen load and distribution on the body of Elaeidobius kamerunicus Faust. (Coleoptera: Curculionidae) within oil palm plantations

Abstract: <p>The African oil palm weevil,<strong> </strong><em>Elaeidobius kamerunicus</em> is an effective pollinator of oil palm. Each individual palm produces exclusively male or female inflorescence so that the success of pollination depends on the ability of the pollinator to transfer pollen from male to female flowers. The objective of this research was to study the amount of pollen carried by <em>E. kamerunicus</em> between male and female inflorescences (pollen load) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Adult weevils of this species carry the highest average number of pollen grains [ 18 , 33 , 52 , 53 , 54 , 55 ]. On average, E. kamerunicus can carry an average of 80,000 to 100,000 pollen grains per visit to the female inflorescence of oil palm [ 55 ]. Ref.…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adult weevils of this species carry the highest average number of pollen grains [ 18 , 33 , 52 , 53 , 54 , 55 ]. On average, E. kamerunicus can carry an average of 80,000 to 100,000 pollen grains per visit to the female inflorescence of oil palm [ 55 ]. Ref.…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
“…Ref. [ 55 ] observed that the amount of pollen carried by E. kamerunicus is positively correlated with their body size, with larger weevils carrying higher pollen loads. Bristles or hairs on the body surface also contribute to higher pollen loads, as reported by studies, such as [ 17 , 18 ].…”
Section: Oil Palm Pollination Agentsmentioning
confidence: 99%
See 3 more Smart Citations